2004
DOI: 10.1249/01.mss.0000135787.73757.4d
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability of Recently Concussed Athletes at Rest and Exercise

Abstract: Low-moderate steady-state exercise elicits a neuroautonomic cardiovascular dysfunction in concussed athletes that is not present in a rested state. This dysfunction alludes to an exercise induced uncoupling between the autonomic and cardiovascular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
189
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(207 citation statements)
references
References 21 publications
12
189
2
4
Order By: Relevance
“…Concussion affects the autonomic nervous system (ANS) 27,28 and the control of both cerebral blood flow (CBF) [29][30][31][32] and cardiac rhythm. 33,34 The primary ANS control center may be damaged in concussion, particularly if a rotational force was applied to the upper cervical spine, 35 as supported by results from a diffusion tensor imaging study 36 that showed changes to brainstem white matter neurons after concussion. The metabolic and physiological dysfunction typically but not always resolves within days to weeks after injury.…”
Section: The Physiology Of Concussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Concussion affects the autonomic nervous system (ANS) 27,28 and the control of both cerebral blood flow (CBF) [29][30][31][32] and cardiac rhythm. 33,34 The primary ANS control center may be damaged in concussion, particularly if a rotational force was applied to the upper cervical spine, 35 as supported by results from a diffusion tensor imaging study 36 that showed changes to brainstem white matter neurons after concussion. The metabolic and physiological dysfunction typically but not always resolves within days to weeks after injury.…”
Section: The Physiology Of Concussionmentioning
confidence: 97%
“…43 Heart-rate variability has been used to quantify autonomic dysfunction across a broad spectrum of TBI severity, including concussion. 33,44,45 Autonomic dysfunction after TBI is believed to represent some degree of uncoupling between the brain autonomic centers and the cardiovascular system, 44 can be precipitated by different types of exercise in patients after concussion, 28,33 and improves as patients recover from severe TBI 46 or from concussion. 28 One group, for example, showed that concussed athletes who reported recent symptom resolution had abnormal HRV 33 and elevated heart rates (HRs) 34 during steady-state exercise (but not at rest) versus healthy controls, which is consistent with increased SNS activation during exercise after concussion.…”
Section: The Physiology Of Concussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, higher HRs have been reported in concussed athletes as a response to exercise, than in matched controls. 31,32 Increases in HR were not observed in the fRW condition, in which the pattern of exercise consisted of two 20 min daily sessions, In contrast to fRW, vRW was ad libitum mostly during the dark phase of PIDs 0-4 and PIDs 7-11. These increases in HR, observed in the FPI-vRW group, are more likely to be reflective of aerobic capacity than of exercise intensity.…”
mentioning
confidence: 89%
“…Only temporal series of more than 256 RR intervals were used for analysis 31 . The RR intervals were exported for analysis by HRV Analysis Software (Biosignal Analysis and Medical Imaging Group, University of Kuopio, Finland) 32,33 . With this program, HRV calculation was performed in the temporal and frequency domains.…”
Section: Monitoring the Cardiovascular Systemmentioning
confidence: 99%